(untitled) (GYMNASIUM, 2017)
The neuromuscular and proprioceptive facilitation techniques, due to their unquestionable effects on the muscles, are successfully used in the recovery of patients with hemiparesis. The purpose of this study is to achieve a proper family, social and professional integration in the new circumstances caused by the disease. The hypothesis which was out starting point is that: if we use mainly facilitation techniques during the recovery programme, we will get some noticeable improvement of coordination compared to the use of the classical recovery methods. The results achieved give us reason to state that the use of facilitation techniques during the recovery of the upper limb coordination in the case of patients with hemiparesis leads to an improvement in the prehension during the daily activities, compared to the results achieved using the classical methods.